2014
DOI: 10.1007/s12011-014-9922-x
|View full text |Cite
|
Sign up to set email alerts
|

Zinc Modulates High Glucose-Induced Apoptosis by Suppressing Oxidative Stress in Renal Tubular Epithelial Cells

Abstract: Hyperglycemia is a characteristic of diabetic nephropathy, inducing renal tubular cell apoptosis by eliciting oxidative stress and inflammation. Zinc (Zn) is known as an essential trace element in many enzymes and proteins involved in antioxidant defenses, electron transport, and exerting antiapoptotic or cytoprotective effects. In this study, the underlying mechanisms involved in the protective effects of Zn on high glucose-induced cytotoxicity were explored using cultured renal tubular epithelial cells (NRK-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 39 publications
1
30
0
1
Order By: Relevance
“…Zinc is vital for numerous cellular processes, including survival, proliferation, aging, apoptosis, autophagy, and differentiation, both in normal and cancer cells [13-16]. As a cofactor for an estimated 3,000 human proteins [17], aberrations in zinc homeostasis contribute to development and progression of human cancers [18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…Zinc is vital for numerous cellular processes, including survival, proliferation, aging, apoptosis, autophagy, and differentiation, both in normal and cancer cells [13-16]. As a cofactor for an estimated 3,000 human proteins [17], aberrations in zinc homeostasis contribute to development and progression of human cancers [18, 19].…”
Section: Introductionmentioning
confidence: 99%
“…13 If the damage is excessive or DNA repair is ineffective, then activation of cell death is the normal physiological response. 12 Although TPEN has been found to inhibit proliferation and induce apoptosis in many cell systems including lymphocytes, 14 epithelial cells, 15 hepatocytes, 16 breast cancer, 17 HT-29 colorectal cancer, 18,19 splenocytes, ovarian cancer, prostate cancer, 20 and pancreatic cancer, 21 its DNA damage potential and mechanisms remain unclear. We have previously shown that the generation of ROS and the redox cycling of copper following TPEN treatment result in targeted cell death of HCT116 human colon cancer cells.…”
Section: Introductionmentioning
confidence: 99%
“…High blood glucose is characteristic of DN [3] . Recent studies have suggested that LOX-1, the primary receptor for binding/uptake of ox-LDL [4] , plays an important role of in the pathogenesis and progression of DN [1,[6][7][8] .…”
Section: Discussionmentioning
confidence: 99%
“…Our study provides the first evidence that high glucose induces LOX-1 and hence enhances oxLDL-induced apoptosis in renal tubular epithelial cells, a key element in the pathogenesis and progression of DN [10,22] . We used primary HRPTEpCs as a cell model in this study, because: (1) tubular dysfunction plays a pivotal role in the development of DN [2] ; (2) high glucose-induced renal proximal tubular epithelial cell apoptosis reportedly serves as a significant factor causing renal functional and pathological changes from DN [2,3] . Compared with the normal control, high glucose concentration-dependently increased the expression of LOX-1 at both the mRNA and the protein levels, which led to increased ox-LDL binding by the cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation